Neonatal central cyanosis caused by anomalous drainage of the right superior vena cava - Saviga Sethasathien (2020)
© 2020 Journal of Cardiovascular Echography | Published by Wolters Kluwer ? Medknow. The draining of the right superior vena cava (SVC) into the left atrium is a very rare anomaly of systemic vein drainage. This case report describes a term male infant presenting with central cyanosis diagnosed with right SVC drainage into the left atrium. The diagnosis was performed using conventional echocardiography and computed tomography angiography. Surgical correction with translocation of the right SVC to the right atrium was necessary to treat the symptom of cyanosis and prevent further complications, including brain abscesses and paradoxical embolization.